Aktivitas Antibakteri Ekstrak Metanol Daun Matenasi (Garcinia Sp.) Terhadap Staphylococcus Aureus dan Eschericia Coli - Diani Mega Sari; Suci Fitriani Sammuli; Tesa Br. Napitupulu; Sri Warni (Yayasan Literasi Sains Indonesia, 2023)
Medicinal plants are very popular among the people of Indonesia as traditional medicinal ingredients. Traditional medicine is a means of supporting public health for generations, long before formal health services and modern medicines touched the layers of society. One of the medicinal plants which is efficacious as a medicine for diarrhea is matenasi leaf (Garcinia sp). Diarrhea is an infectious disease that often occurs in Indonesia due to Escherichia coli bacteria. This study aims to determine the antibacterial activity of methanol extract using the paper disc diffusion method which is dripped with 10 µl of the test solution using a micro pipette. The concentrations of the methanol extract used were 50%, 75%, and 100% compared to the positive control, namely 30 µl chloramphenicol solution. Matenasi leaves using methanol extract have strong antibacterial activity at a concentration of 100%. For Staphylococcus aureus bacteria with a concentration of 100% with a diameter of 22.67 mm (very strong category), Escherichia coli bacteria with a concentration of 100% with a diameter of 18.25 mm (strong category). The methanol extract of matenasi leaves has the potential as an antibacterial against Stapylococcus aureus and Escherichia coli bacteria.